HUBUNGAN ANTARA PENGETAHUAN IBU MENGENAI KMS BALITA DENGAN SIKAP IBU DALAM UPAYA KESEHATAN BALITA DI DESA TURIREJO WILAYAH KERJA PUSKESMAS JEPON KECAMATAN JEPON KABUPATEN BLORA - Warijan Warijan; Titi Suherni (Jurnal Kebidanan, 2012)
HUBUNGAN ANTARA PENGETAHUAN IBU MENGENAI KMS BALITA DENGAN SIKAP IBU DALAM UPAYA KESEHATAN BALITA DI DESA TURIREJO WILAYAH KERJA PUSKESMAS JEPON KECAMATAN JEPON KABUPATEN BLORA Warijan & Titi Suherni Poltekkes Kemenkes Semarang ABSTRAK Mother Knowledge of concerning babies KMS is representing one of appliance monitor the condition of health baby, very important to increase the role and also mother in the effort of her childs health. Based on the writer perception, although have a lot of KMS allotted to society, the content and masegge of existing health in KMS is not understood yet about heavy graph of body, growth baby etc. To knowtherelation of among knowledge of Mother hitting KMS baby behaviorally Mother in the effort health baby. this Research Device is cross sectional, executed in Turirejo Village, Work Regional Puskesmas Jepon, Sub district of Jepon, Regency of Blora. Subject of mother Research having baby age12-60 month. Sample taken by as much 60 people, witht hetecnique of proportional of sampling and member election by random is sampling. Data intake conducted by using is test driving the questioners. Questioners Knowledge composed by 20 item of composed by behavioral and quesioners statement 25 statement item. To know the existence of relation of among knowledge behaviorally, analyzed with the statistical analysis technique of Chi Square and Product Moment Correlation program the SPSS11 at belief storey ; level 95%. Showing the existence of relation having a meaning of among know ledge of Mother hitting babies KMS behavior Mother in the effort health babies (X2 = 28,01 and p value =0,01). Knowledge picture Ms. knowledgeable Lower and behavioral picture Ms. which good a behavior. More amounts compared to which unfavorable is behavior. There is relation having a meaning of among mother knowledge of concerning babies KMS behaviorally is mother in the effort health babies, by p is value = 0,01 Keyword : Knowladge, Behavioral, KMS Body, Strive the Health Baby